2020
DOI: 10.1007/s42729-020-00343-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantified Benefits of Cultivating Day-Lily (Hemerocallis citrina) Hedgerows over Multiple Years on Sloped Red-Soil Farmland, Southern China

Abstract: Planting hedgerows is an effective measure for increasing soil and water conservation on sloped farmland, although the comprehensive and dynamic changes in benefits across the life span of the hedgerow are not fully understood. To expand our understanding in this area, day-lily (Hemerocallis citrina) was selected to research the effect of hedgerows built on sloped red-soil farmland in southern China. In situ observations of runoff and soil loss from 2012 to 2018 were recorded in triplicate for two treatments: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Our results were consistent with these earlier mentioned studies, and we observed that all four hedgerow patterns can increase the soil nutrient content to different degrees, which, however, differs from the results of Zheng. They carried out a hedgerow-crop intercropping experiment during 2012–2018 and discovered that the TN, TP, and SOM contents recorded in the hedgerow plots showed unclear variation trends relative to the control plot, by being slightly high or low at one time or another, thereby having little effect on the total nutrient content in the topsoil [ 14 ]. This was mainly due to the differences in environment, cultivation management, and hedge species and the lack of competition of crops for soil nutrients in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were consistent with these earlier mentioned studies, and we observed that all four hedgerow patterns can increase the soil nutrient content to different degrees, which, however, differs from the results of Zheng. They carried out a hedgerow-crop intercropping experiment during 2012–2018 and discovered that the TN, TP, and SOM contents recorded in the hedgerow plots showed unclear variation trends relative to the control plot, by being slightly high or low at one time or another, thereby having little effect on the total nutrient content in the topsoil [ 14 ]. This was mainly due to the differences in environment, cultivation management, and hedge species and the lack of competition of crops for soil nutrients in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Hedgerows have been widely used on slope farmlands in China and abroad in social production due to their water and soil conservation effects, such as soil erosion reduction and non-point-source pollution control [ 14 , 15 , 16 , 17 ]. Overground and underground hedgerows contribute to 62.25 and 37.75% of runoff reduction along with 60.44 and 39.56% of the sediment reduction advantages on average, respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The red soil hilly region of southern China is an important agricultural production area [17], accounting for 36% of the total cultivated land and more than 50% of the total output of oil-bearing crops, grain, and agricultural in China [18]. The red soil sloping farmland developed from the weathered granite parent materials is widely distributed here and is the primary source of soil erosion [19,20], and the soil loss rate can reach 98.78 t ha −1 yr −1 . There is a large total amount of rainfall in this area but with extremely uneven distribution of temporality and spatiality.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many scholars from both China and overseas have done a lot of scientific research on the ecological isolation zone, mainly focusing on the anti-erosion performance of the soil [7][8][9][10], the nutrient change of the ground [11][12][13][14], the soil microbial community [11,15,16], the stability of the soil aggregate structure [17][18][19] and the interception of pollutants [8,[20][21][22][23] after the ecological isolation zone. In contrast, there are fewer studies on the response of herbaceous vegetation communities and soils in terraces of ecological isolation zones in the mountain red soil area, and there are no studies and evaluations on the maintenance and monitoring of ecological isolation zones after their installation.…”
Section: Introductionmentioning
confidence: 99%